Entrepreneurship shaping the business environment in rural areas evaluation of the service of subjects - Alieva Gulnura Alievna; Erniyazov Aliysher Karamurza Ogli; Eldashbaev Muratbek Amanbay Qizi (Zien Journals, 2023)
The article analyzes the organizational and economic mechanisms of the development of small business and private entrepreneurship in rural areas, and gives conclusions and recommendations
Keywords: Small business; business environment; entrepreneurship